CULTURAL SHOCK: SOCIAL AND PSYCHOLOGICAL ADAPTATION TO THE NEW CULTURAL ENVIRONMENT - O. Kulikova (Вестник университета)
In article the concept of «cultural shock», the reasons and the main signs of emergence of this state are considered. Stages of cultural adaptation, causes and effects of social psychological state of the person, being in others country are considered. A result of article is descriptions of possible strategies of cultural adaptation.